Investigation of Thermophysical and Rheological Properties of Scallop Shell Powder/SAE 5w-30 Nanolubricant - Purwanto, Muhammad Rizky; Puspitasari, Poppy; Permanasari, Avita Ayu; Abdullah, Muhammad Ilman Hakimi Chua (Universitas Merdeka Malang, 2023)
Nanolubricant is a type of nano fluid that contains base-fluid lubricant (water or oil) and nanoparticles. This study aims to analyze the thermophysical and rheological properties of lubricants with the addition of nanoparticles. The nanoparticles used are Calcium Carbonate (CaCO3) made from scallop shell waste. The base lubricant is SAE 5W-30 synthetic oil which has quite good performance. Synthesis of Calcium Carbonate (CaCO3) into SAE 5W-30 lubricant uses a two-step method. Variations in the addition of volume fraction of Calcium Carbonate (CaCO3) of 0.05%, 0.10%, 0.15%. Furthermore, the nanolubricant was tested for its thermophysical properties which included thermal conductivity, specific heat, density, viscosity, and sedimentation. After that, the rheology of the nanolubricant can be known from the viscosity data by calculating the shear rate and shear stress.